Ergonomic aspects of the learning process - Andziulienė, Beatričė; Valionienė, Elena (Lietuvos matematikos rinkinys, 2009)
This paper is about ergonomic education process’ organization. Authors analyze main educational principles of ergonomic education process on the basis of individual educational environment creation in the electronic environment. There are given some recommendations in this paper. These recommendations are about ergonomic education material preparation, training process making more effective.
Keywords: ergonomics; ergonomic education; distance education; personal training environment; e-learning